Research on Python Language Teaching Based on Case - Xiong, Taisong; Huang, Yuanyuan (Scholars Journal of Arts, Humanities and Social Sciences, 2021)
Python language is a more and more widely used programming language. It becomes an inevitable choice to chose Python language as an undergraduate programming language teaching. Aiming at the current Python language teaching, focusing on basic grammar explanations, lack of case-based and comprehensive application of knowledge points. We propose a case-based python teaching plan, and these cases include comprehensively Python grammar knowledge to effectively enhance students' learning interest and learning effect.